Tax Evasion: System Justice, Distrust To Fiscus, And Love Of Money - Listya Sugiyarti; Desiana; Sri Nitta Crissiana Wirya Atmaja (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
The research aims to determine system justice, distrust to fiscus and love of money towards tax evasion. The sample in the study are individual taxpayers in the area of the Ciawi Pratama Tax Office who are conducting taxation activities. The type of data is quantitative data. The data collection method used is the questionnaire method. The sampling technique of 100 individual taxpayers use purposive sampling. For Data processing usage is Statistical Package for Social Science. The results of the study indicate that system justice has a negative effect on tax evasion, distrust to fiscus influences on tax evasion, while the love of money infuences tax evasion. Keywords: System Justice, Distrust to Fiscus, Love of Money, Tax Evasion.